2023
DOI: 10.1002/14651858.cd012746.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Personalised interventions for subgroups of children with conduct problems

Abstract: Personalised interventions for subgroups of children with conduct problems (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…However, meta-analyses which examined interventions that included behavioral and non-behavioral elements still revealed small to moderate effect-sizes for externalizing symptoms (Bakker et al, 2017 ). Beyond this, one meta-analysis also found that personalized interventions led to a slightly greater improvement in child conduct problems compared to non-personalized interventions, as measured through the ECBI Problem Subscale in the short term, but not for other outcome measures (Lane et al, 2023 ). However, conclusions are limited as the study was considered low quality.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, meta-analyses which examined interventions that included behavioral and non-behavioral elements still revealed small to moderate effect-sizes for externalizing symptoms (Bakker et al, 2017 ). Beyond this, one meta-analysis also found that personalized interventions led to a slightly greater improvement in child conduct problems compared to non-personalized interventions, as measured through the ECBI Problem Subscale in the short term, but not for other outcome measures (Lane et al, 2023 ). However, conclusions are limited as the study was considered low quality.…”
Section: Resultsmentioning
confidence: 97%
“…A total of 11 reviews (seven meta-analyses and four systematic reviews) of mostly moderate to high quality examined mixed psychosocial interventions for externalising symptoms (Bakker et al, 2017 ; Barlow & Stewart-Brown, 2000 ; Battagliese et al, 2015 ; Burkey et al, 2018 ; Comer et al, 2013 ; Connor et al, 2006 ; Fossum et al, 2008 , 2016 ; Lane et al, 2023 ; Stoltz et al, 2012 ; Tse, 2006 ). Of these studies, quality was lower for Lane ( 2023 ) and Tse ( 2006 ), which were rated low. Meta-analyses showed that behavioral-based interventions had greater efficacy than non-behavioral-based interventions (Comer et al, 2013 ; Fossum et al, 2008 , 2016 ).…”
Section: Resultsmentioning
confidence: 99%